Culture - Theory - Disability Encounters between Disability Studies and Cultural Studies - Waldschmidt, Anne; Berressem, Hanjo; Ingwersen, Moritz (transcript Verlag, 2017)
Which theoretical approaches of contemporary cultural criticism can Disability Studies employ? At the same time, what can Cultural Studies gain by incorporating disability more fully as a framework for critical analysis? This international collection of essays enriches the thriving discourse of Cultural Disability Studies by offering stimulating dialogues between British, Czech, German and US-American scholars. In order to contour the various 'contact zones' between the two fields, the volume works transdisciplinarily, drawing on fields such as sociology, literary studies, art history and philosophy.
Description based on print version record.
KU Select 2016 Front List Collection
Keywords: Social Science; Social Science / People With Disabilities; Social sciences; Electronic books